2021
DOI: 10.4068/cmj.2021.57.1.7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Mental Health of Vulnerable Two Groups: Developmental Trauma of the Child-Adolescents and Work Disaster of Health Care Workers

Abstract: COVID-19 has spread worldwide. People are struggling to adjust to a new normal, but changes in their daily routines are also causing stress. A person may feel depressed, uneasy, or suicidal and may complain of symptoms such as panic attacks, post-traumatic stress disease (PTSD), psychosis, obsessive–compulsive disorder, or paranoia when personal resilience cannot effectively process the stress. Children, adolescents, and health care workers are especially psychologically vulnerable groups in the pandemic calam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Studies in other countries support this insight. 20 , 21 Our study reported an almost similar percentage of participants with normal to mild depression and stress, and a higher rate (40.9%) of recovered HCWs with at least moderate anxiety than Tee et al (26.6%). 11 Zahoor et al 27 reported that there appears to be no significant difference in the relative risk of developing depression and anxiety among recovered versus non-infected HCWs, although a longitudinal study to monitor the development of these psychological effects over time may be necessary.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies in other countries support this insight. 20 , 21 Our study reported an almost similar percentage of participants with normal to mild depression and stress, and a higher rate (40.9%) of recovered HCWs with at least moderate anxiety than Tee et al (26.6%). 11 Zahoor et al 27 reported that there appears to be no significant difference in the relative risk of developing depression and anxiety among recovered versus non-infected HCWs, although a longitudinal study to monitor the development of these psychological effects over time may be necessary.…”
Section: Discussionsupporting
confidence: 55%
“…This population also faces a higher degree of stigmatization and mental health vulnerability in the community. 21 In two studies, researchers found higher levels of posttraumatic stress symptoms among recovered HCWs compared to the general population of survivors. 22 , 23 Fatigue, depression, and anxiety appear to be significant symptoms after recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This has led many countries to implement different containment measures to reduce the spread of the virus [ 5 ]—social distancing, restriction of movement and the use of masks—which, together with the fear of contagion, concern for the safety of oneself or one’s loved ones, and the economic problems derived from these measures, has caused people to face previously unknown psychosocial situations. This has increased the risk of mental health problems such as anxiety, depression, and stress [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus (COVID-19) pandemic started with the outbreak in China in 2019, and as of May 2023, it has affected roughly 687 million people globally, causing almost 6.87 million deaths [1]. Besides health and economic crises, scientists also pointed out the pandemic's adverse psychological effects [2], and adolescents were identified as one of the most vulnerable groups [3]. The central premise of this study refers to the protective role of self-compassion and its potential to decrease the stress of older adolescents during the COVID-19 pandemic [4] and promote positive thinking, all of which diminish mental health problems.…”
Section: Introductionmentioning
confidence: 99%